PENINGKATAN PEMAHAMAN KEPUTUSAN MARGINAL DENGAN PENGGUNAAN MODEL KAKI KIRI DAN COKLAT - Muhammad Efrin Sofyan (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
This study aims to improve the competence of students through the use of the left foot model and brown roca in the subject of marginal decision material economics. The subjects of the learning actors of class XI PSIS Economics teachers and the subjects receiving the actions were students of class XI PSIS, semester I of the 2019/2020 academic year of SMA Plus Negeri 17 Palembang. Data were collected through observation, and test data for the left foot and brown model. The validity of the data was checked with the help of other observers through observation tables. Cycle 1, the percentage of students who were not active was 6.77% the remaining 93.23% were active. Based on the test results of students, it can be seen that 12 students (63%) have not met the minimum completeness criteria while 7 students (37%) have met the minimum completeness. The average marginal decision ability in the first cycle was 82.83. In the second cycle, 9.02% of the activity was good, and 90.98% of the activity was very good. Furthermore, looking at the results of the left foot and brown roca marginal decisions, 100% of the students had finished, and the activeness of the students. From the application of the actions in cycles 1 and 2, it can be concluded that it turns out that the use of the left foot and brown model can improve students' competence in the Economics Subject Marginal Decision Material The results of this PTK are expected to find a suitable model for Marginal Decision competences